INTRAEMPREENDEDORISMO E CULTURA DA INOVAÇÃO: UMA RELAÇÃO DE INTERDEPENDÊNCIA - ROVEA, ADRIANE LUCI FERREIRA (2022)
Observing the current scenario, the knowledge of intrapreneurship has been gaining prominence, mixing the need of the employee and the organization to adapt to competitive environments, constantly influenced by the variables of the internal and external environment. Starting from the premise that intrapreneurship is a great innovation accelerator, the challenge for organizations of any nature or size is to create means and opportunities for intrapreneurs to seek and implement these visions, which must be aligned with the company's strategy. The objective of this research is to analyze organizational practices and initiatives that stimulate intrapreneurship in command positions in the industry area in an industrial unit in Guarapuava-PR. The delimitation of the study will be carried out in the area of industrial production that seeks continuous improvement and operational excellence, since it is through people that innovation becomes a habit, taking into account the leaders individual behavioral skills, taking into account their positions, with regard to the maintenance of the company's competences. It is, therefore, a qualitative research, classified as an exploratory-descriptive case study, in which interviews were used as the main source of data collection, as well as systematic observation and field diary. Three categories of analysis composed of twelve units of meaning were also created. Category 1, refers to the company's relationship with innovation and the importance of organizational culture as a source of incentives for intrapreneurial behavior; Category 2 refers to the intrapreneurial behavior of production leaders; Category 3 deals with the composition of organizational factors of stimulus or barrier to intrapreneurial behavior Content analysis was used to analyze the data obtained through interviews. In the analysis of intrapreneurial behavior, the software-R/Studio was also used, using the Likert package. The results were that intrapreneurship is a strategy used to increase the efficiency of organizations with traditional management structures and verified the evolution of the implementation of the new management in the company, so it is important that the company object of study continues in this process, looking at the culture of intrapreneurship and incorporating the values and principles of intrapreneurship, demonstrating to its employees that the organizational image assumed by managers becomes practical.